Gestational biomarkers of daughter’s breast cancer in the Child Health and Development Studies - Cirillo, Piera M. (Reprod Toxicol, 2019)
We examined the link between gestational biomarkers and breast cancer in 9169 daughters born into the Child Health and Development Studies from 1959 to 1967. We identified 137 breast cancer cases diagnosed by age 52 as of 2012. Markers of increased risk included higher placental volume and rapid 2nd trimester gestational weight gain. Protective markers were placental hemorrhage and fibrin deposition, indicators of resistance to placental trophoblast invasion. Paradoxically, higher ponderal index at birth was protective suggesting that fetal and placental pathways to breast cancer are multiple and distinct. Results link placental and fetal phenotypes to breast cancer, characterizing some as restrictive and others as permissive markers of tumor development. We found new biomarkers of breast cancer risk that can be mined to discover ‘omic correlates in the pregnancy exposome using archived and contemporary pregnancy samples. This line of investigation may discover new pathways to risk and new opportunities for prevention.